Criminal liability for illegal destruction of forest plantations - Korneev Sergey; Avdeev Sergey; Kozhina Yulia; Kutukov Sergey (BIO Web of Conferences)
Russia’s forests, occupying one-fifth of the world’s forest area and being one of the renewable natural resources, meet multiple needs of the economy and society for forest resources, performing the most important environmental, protective and other useful functions. The problems of forest protection and utilization are becoming increasingly diverse and complex. Illegal felling of forest plantations is one of the most widespread crimes provided for in Chapter 26 of the Criminal Code of the Russian Federation and accounts for ½ of the total number of socially dangerous acts causing or threatening to cause damage to the environment. According to experts, it is practically impossible to fully restore the forest fund damaged by illegal logging. This is primarily due to the time required to replace lost trees and shrubs, which ranges from 81 to 120 years and more for coniferous and deciduous species of seed origin, and from 41 to 70 years and more for coniferous and deciduous species of shoot origin. Reforestation requires high material costs. The objective of this research is to develop new and optimize existing approaches to counteract the illegal destruction of forest plantations. In order to achieve the desired goal, the research sets and consistently solves the following objectives: to analyze the legal norms determining the limits of legal responsibility for illegal felling of forest plantations; to determine the place of illegal felling of forest plantations in the structure of environmental crimes; to study the statistical data on the number of registered environmental crimes, convicted persons for committing environmental crimes in general and for illegal felling of forest plantations in particular; to consider the doctrinal approaches to the subject of this research; to develop the author’s proposals on the legal regulation of the fight against illegal felling of forest plantations; to develop the author’s proposals on the legal regulation of counteraction to illegal destruction of forest plantations.